Charlie's Surf Resort and Academy - Lagman, Jovanne R.
Charlie's Surf Resort and Academy is a surf complex located in the next big development of Baler, Aurora. This thesis aims to come up with a design integrating two concepts, the recreational and learning side of surfing while providing opportunities for better surf education for all levels and users. The focus of this thesis is the new learning experience for surfing in the Philippines, at the same time maximizing Baler as one of the prime location for surfing.